Determinant of Kualitas Sustainability Report (Studi Empiris Perusahaan Pertambangan yang terdaftar di BEI periode 2022-2024) - Kartika Suryanengsih; Maylia Pramono Sari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research is motivated by the rising sustainability issues and the phenomenon of greenwashing in the mining sector, which demand better transparency and quality in sustainability reports. This study aims to analyze the influence of shareholder pressure, employee pressure, and government pressure on the quality of sustainability reports using legitimacy theory, while examining the role of profitability as a moderating variable and firm size as a control variable. The study employs a quantitative approach, focusing on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research sample was obtained through purposive sampling, resulting in 138 observations, and was analyzed using panel data regression. The results show that employee pressure and government pressure have a positive and significant effect on the quality of sustainability reports, while shareholder pressure has no significant effect. Furthermore, profitability is proven to moderate the relationship between employee pressure and sustainability report quality in a negative direction, but it does not moderate the influence of shareholder or government pressure. These findings indicate that the improvement of sustainability reporting quality in the mining sector is more influenced by internal demands and regulatory pressure than by shareholders' financial orientation, suggesting that sustainability reports still function as a corporate legitimacy instrument in responding to specific stakeholder pressures.